Malignant epithelioma of the liver. Issue 667 (May 1981) - Burroughs, A. K.; Barter, S. J.; Jenkins, W. J.
Abstract : Carcinoma complicating congenital cystic conditions of the liver is rare. The authors report a primary malignant epithelioma of the liver in association with multiple intrahepatic biliary cysts, which are not usually considered to predispose to malignancy.